(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Hemodialysis water and dialysates are fundamental in the treatment of kidney disease. During just one hemodialysis session, 120 liters of dialysate are consumed. Thus, it is essential that the parameters of chemical and microbiological quality of the fluids used in dialysis systems are carefully observed. In this study, water samples were collected at 12 hospitals in the state of Rio de Janeiro. The samples were obtained at three points of fluid reservoirs: pre-, post-osmosis and dialysis solution. After collection, colony forming units (CFU), total coliforms and Escherichia coli 100 mL-1 were quantified. Later, isolated colonies and endotoxin content were identified by biochemical assays. Data about total aluminum levels per sample (mg L-1) were also obtained. Samples of all mobile dialysis services and points of collection were contaminated above the levels set out by national laws, in particular by Pseudomonas aeruginosa. Endotoxin levels were also above the recommended by current legislation (> 0.25 EU mL-1). Only three samples contained detectable levels of aluminum, which were found to be above the recommended values for the corresponding resolution (0.01 mg L-1). Finally, there were no observable amounts of total coliforms and E. coli 100 mL-1 sample. The data from this study are an important step forward in the standardization and control of chemical/microbiological quality of mobile dialysis services.